1993
DOI: 10.3109/10428199309147352
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Epstein-Barr Virus Subtypes in Human Immunodeficiency Virus-Associated Lymphoma

Abstract: High grade B cell non-Hodgkin's lymphoma (NHL) is an increasingly important problem in individuals infected with the human immunodeficiency virus (HIV). Fifty percent of these tumours harbour the Epstein-Barr virus (EBV) and there is an equal frequency of EBV A and B-subtypes in the tumours. This contrasts with the recent report that only A-type EBV is associated with Hodgkin's disease. Such studies are challenging the traditional models of EBV-associated lymphomagenesis and showing the way for further studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2

Year Published

1995
1995
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 48 publications
2
33
2
Order By: Relevance
“…rrez and others Most isolates of EBV are type I, but type II virus was reported, in a study from Memphis, USA, to be frequently found in OS (Sixbey et al, 1989). Type II EBV has been shown to be present in 40-50 % of EBV-associated endemic BL and AIDS-associated lymphomas and lymphomas in the immune-compromised host (Goldschmidts et al, 1992 ;Boyle et al, 1991). Recently, we and others have described variations in the EBNA-1 sequence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…rrez and others Most isolates of EBV are type I, but type II virus was reported, in a study from Memphis, USA, to be frequently found in OS (Sixbey et al, 1989). Type II EBV has been shown to be present in 40-50 % of EBV-associated endemic BL and AIDS-associated lymphomas and lymphomas in the immune-compromised host (Goldschmidts et al, 1992 ;Boyle et al, 1991). Recently, we and others have described variations in the EBNA-1 sequence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, EBV infection in PEL resembles infection of other EBV-positive lymphomas developing both in humans and in animal models. 33,35,[40][41][42][43][44] In the case of AIDS-related PEL, it is notable that one single EBV strain infects the lymphoma clone, whereas multiple EBV strains are harbored by peripheral blood mononuclear cells of HIV-infected individuals (this study and Refs 36 and 37).…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from PBMC by routine methods (Sambrook et al, 1989). To detect the presence of EBV DNA in samples, PCR was carried out using primer sets which amplify sequence of the EBV genome within the EBNA2 gene (Boyle et al, 1991). The sensitivity of the primers was determined using Namalwa, an EBVpositive Burkitt's lymphoma (BL) cell line which is known to carry one or two integrated EBV genomes per cell (Henderson et al, 1983).…”
Section: Methodsmentioning
confidence: 99%